What can food policy do to redirect the diet transition? - Haddad, Lawrence J. (International Food Policy Research Institute, 2003)
The dietary transition in the developing world is accelerating toward an increased burden of chronic disease. It is increasing human mortality and disease burdens, and it is lowering economic productivity. The dietary transition is driven by changing preferences fueled by growing incomes, changing relative prices, urbanization, and food technology and distribution systems. This paper identifies policy options from the food supply and demand sides that can influence the transition toward increasingly healthy outcomes. These options have had mixed success in industrialized countries, and the policy tradeoffs in the developing world will be even more complicated. Additional technical research is needed to assess competing risks and help develop policy options. There is also a need for research to engage different actors in the policymaking process. In a debate in which much is at stake, there is a potentially powerful role for researchers to bring these actors to the table.